Experimental Therapeutic Approaches for the Treatment of Retinal Pathology in Neuronal Ceroid Lipofuscinoses - Bartsch, Udo; Storch, Stephan (Frontiers in Neurology, 2022)
The neuronal ceroid lipofuscinoses (NCLs) are a group of childhood-onset neurodegenerative lysosomal storage disorders mainly affecting the brain and the retina. In the NCLs, disease-causing mutations in 13 different ceroid lipofuscinoses genes (CLN) have been identified. The clinical symptoms include seizures, progressive neurological decline, deterioration of motor and language skills, and dementia resulting in premature death. In addition, the deterioration and loss of vision caused by progressive retinal degeneration is another major hallmark of NCLs. To date, there is no curative therapy for the treatment of retinal degeneration and vision loss in patients with NCL. In this review, the key findings of different experimental approaches in NCL animal models aimed at attenuating progressive retinal degeneration and the decline in retinal function are discussed. Different approaches, including experimental enzyme replacement therapy, gene therapy, cell-based therapy, and immunomodulation therapy were evaluated and showed encouraging therapeutic benefits. Recent experimental ocular gene therapies in NCL animal models with soluble lysosomal enzyme deficiencies and transmembrane protein deficiencies have shown the strong potential of gene-based approaches to treat retinal dystrophies in NCLs. In CLN3 and CLN6 mouse models, an adeno-associated virus (AAV) vector-mediated delivery of CLN3 and CLN6 to bipolar cells has been shown to attenuate the retinal dysfunction. Therapeutic benefits of ocular enzyme replacement therapies were evaluated in CLN2 and CLN10 animal models. Since brain-targeted gene or enzyme replacement therapies will most likely not attenuate retinal neurodegeneration, there is an unmet need for treatment options additionally targeting the retina in patients with NCL. The long-term benefits of these therapeutic interventions aimed at attenuating retinal degeneration and vision loss in patients with NCL remain to be investigated in future clinical studies.